Crusader archaeology the material culture of the Latin East - Boas, Adrian J. 1952-
"The third edition of Crusader Archaeology updates previous editions to include coverage of important recent work in the field. It examines what life was like for European settlers and travellers to the crusader states during the centuries of Latin rule. Examining past, recent and ongoing archaeological discoveries, and research in the field from Israel, Jordan, Syria, Turkey, and Cyprus the volume includes recent findings and approaches including new exploration work in urban sites such as Jerusalem, Acre and Caesarea, new work on industrial sites and new discoveries in research including DNA studies, the field of weaponry and many other topics. It covers such topics as settlement types, fortification, daily life, day-to-day activities, warfare, religious life, arts, industry, leisure pursuits, building technology, agriculture, medicine, death and burial. It considers, in all these fields, the manner in which the Frankish population was influenced by the local and neighbouring populations, and how, in many of their endeavours, the Franks evolved and developed their own, unique and often remarkably advanced material culture. Together with the archaeological evidence, Crusader Archaeology provides a historical background to the various topics in order to provide context to each of the discussions. Crusader Archaeology remains the only comprehensive study of the architecture and material finds of the Crusader period. This well-illustrated volume serves as a basic textbook for students and scholars with an interest in the Middle Ages and in particular the Crusades and the Latin East"--
Keywords: Geschichte 1075-1570; Geschichte 1050-1500; Archäologie; Kultur; Kreuzzüge; Kunst; Sachkultur; Kreuzfahrerstaaten; Naher Osten; Jerusalem / History / Latin Kingdom, 1099-1244; Crusades / Influence; Jerusalem / Antiquities; Excavations (Archaeology) / Jerusalem; Latin Orient / Social life and customs; Jérusalem (Royaume latin, 1099-1244); Croisades / Influence; Jérusalem / Antiquités; Fouilles (Archéologie) / Jérusalem; Orient latin / Murs et coutumes; Antiquities; Excavations (Archaeology); Manners and customs; Middle East / Jerusalem; Middle East / Latin Orient; 1099-1244; History